THE EFFECT OF FINANCIAL LITERATURE, MOTIVATION, AND RISK ON INVESTMENT IN INDONESIA THROUGH THE IMPACT OF COVID-19 AS INTERVENING VARIABLES - Jufriadi Jufriadi (Universitas Islam Negeri Alauddin Makassar, 2021)
This study aims to determine the effect of financial literacy, motivation, and risk on investment in Indonesia through the impact of covid-19 as an intervening variable. This research is a descriptive study that tries to explain the effect of each variable based on references and previous research results. In general, based on the theory and the results of previous research, it shows that financial literacy and motivation greatly affect the desire to invest in Indonesia as well as the risk that does not affect investment because it is a factor that must be anticipated by economic actors. However, the impact of COVID-19 has caused investment in Indonesia to be greatly affected.